Analisis Penerimaan SIMRS Rumah Sakit TK IV DKT Kediri dengan Technology Acceptance Model - Eva Firdayanti Bisono; Krisnita Dwi Jayanti; Putri Indra Suryandari; Nurhadi Nurhadi; Agustinus Nugroho Pudji Lestarjo; Sonia Ghaniy Anassya (Politeknik Negeri Jember, 2024)
The Hospital Information System (SIMRS) integrates the entire process of hospital services through information technology. The transition from the old system to the new one developed by a vendor requires a transition process due to SIMRS still requiring manual data input. This study aims to analyze the acceptance of SIMRS in the medical record unit using the TAM method. The research method employed is quantitative descriptive with purposive sampling technique involving 4 medical record staff. Data was collected through questionnaires. The research results indicate that the percentage calculation of perceived ease of use (84.16%), perceived usefulness (80%), Attitude toward using (73%), behavioral intention (87.50%), and actual usage (80%) falls under the category of strongly agree. It is hoped that the TK IV DKT Kediri Hospital will provide periodic training on SIMRS usage, especially for staff members using SIMRS, and enhance the completeness of SIMRS features in the future.